2005
DOI: 10.2166/wqrj.2005.034
|View full text |Cite
|
Sign up to set email alerts
|

Site Fidelity of Mummichogs (Fundulus heteroclitus) in an Atlantic Canadian Estuary

Abstract: The site fidelity of mummichogs (Fundulus heteroclitus) within the upper Miramichi River estuary, New Brunswick, Canada, was investigated to assess the value of using this fish as a sentinel species for monitoring effects of point source anthropogenic effluents such as pulp and paper mill effluent. During the ice-free season (May to November) of 2002, 4123 adult mummichogs (>30 mm TL) were captured, by beach seine and minnow trap, biweekly from four sites within the estuary. Fish were marked intramuscul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 39 publications
4
36
0
Order By: Relevance
“…Lotrich 1975, Teo & Able 2003, Skinner et al 2005. This confirms that individuals of both the northern (macrolepidotus) and southern (heteroclitus) sub-species of Fundulus heteroclitus have a general tendency to exhibit a small (<1 km) home range.…”
Section: Field Recapture Ratessupporting
confidence: 68%
See 1 more Smart Citation
“…Lotrich 1975, Teo & Able 2003, Skinner et al 2005. This confirms that individuals of both the northern (macrolepidotus) and southern (heteroclitus) sub-species of Fundulus heteroclitus have a general tendency to exhibit a small (<1 km) home range.…”
Section: Field Recapture Ratessupporting
confidence: 68%
“…The mummichog is a relatively small (adult size <12 cm) species found primarily along shallow estuarine shorelines (Bigelow & Schroeder 1953). It is not a strong swimmer and has a limited home range of less than 1 km (Skinner et al 2005, Able et al 2006). Spawning and primary nursery habitats are in the intertidal zone (Kneib 1997).…”
Section: Abstract: Coded Wire Tags · Estuary · Genome · Fundulus Hetmentioning
confidence: 99%
“…Direct estimates of adult dispersal distance are not known for F. grandis. Mark-recapture dispersal estimates for the closely related F. heteroclitus, which inhabits salt marshes along the Atlantic coast of North America, ranged from 200 m to 3.6 km within a single year (Sweeney et al 1998, Skinner et al 2005. If the genetic structure of F. grandis is predominantly shaped by current-day dispersal and distributional patterns, we would expect to find a pattern of IBD across the Gulf with significant genetic differentiation among populations due to low levels of dispersal.…”
Section: Introductionmentioning
confidence: 99%
“…However, the other restoration site, Bull Island, is separated from these 2 sites by the leveed main channel of the Napa River, making it less likely that there is an exchange of free-swimming juvenile fish between this and other marshes. Numer-250 Cohen & Bollens: Diet and growth of Mississippi silversides and yellowfin gobies ous estuarine and salt marsh studies have shown that both juveniles and adults of several wetland species display strong site fidelity to local intertidal marsh creeks (Potthoff & Allen 2003, Teo & Able 2003, Skinner et al 2005. Concurrent investigation of the wetland food web at our study sites using stable isotopes also suggests that both yellowfin gobies and Mississippi silversides display some measure of site fidelity and that fish diet bases at Bull Island were significantly different than those at Coon Island and Pond 2A (Howe & Simenstad 2005).…”
mentioning
confidence: 99%